HERC database of mapping studies, Version 9.0 - Dakin, H; Abel, L; Burns, R; Koleva-Kolarova, R; Yang, Y (University of Oxford, 2023)
The database presents details of the sample size, modelling methods and patient population, in addition to the citation details and source instruments that are mapped in each of the 246 studies meeting the inclusion criteria. An article summarising the methods of the literature review and the results of version 6.0 has been published in Health and Quality of Life Outcomes (https://doi.org/10.1186/s12955-018-0857-3), updating the older article on version 2.0 of the database. The current version (9.0) is based on searches conducted in January 2023; the database will be updated approximately annually as new studies are published. This database lists published primary studies estimating mapping algorithms that estimate EQ-5D utilities from other quality of life measures and report the algorithm in sufficient detail to allow other researchers to estimate utilities on other data.